Does direct democracy reduce the size of government? : new evidence from historical data, 1890 - 2000 - Patricia Funk; Christina Gathmann (Center for Economic Studies and ifo Institute (CESifo), 2009)
Using a new dataset of Swiss cantons from 1890 to 2000, we estimate the causal effect of direct democracy on government spending. Our analysis is novel in two ways: first, we use fixed effects to control for unobserved heterogeneity; second, we combine a new instrument with fixed effects to address the potential endogeneity of institutional reform. We find that direct democracy has a constraining, but modest effect on spending. Our estimates suggest that a mandatory budget referendum reduces canton expenditures by 9 percent. A decline in the signature requirement for the voter initiative by one percent reduces spending by 2.2 percent. We find no evidence that direct democracy at the canton level results in higher local spending or a more decentralized government.
Keywords: 330; Demokratie; Referendum; Öffentliche Ausgaben; Teilstaat; Staatsquote; Schweiz